Factors affecting knowledge sharing behaviour in public higher education institutions: An empirical study of Vietnam - Du Thi Chung; Pham Thi Tram Anh (Cogent Business & Management, 2022)
The purpose of this study is to examine the factors that promote or discourage knowledge-sharing behaviour among academic staff in higher education institutions. The main objective of this study was to investigate the effects of organizational factors and personality on knowledge-sharing behaviour. Utilizing three main theories-those of social capital, social cognition, and social exchange, this study developed a theoretical model that unveiled two critical dimensions: psychological and organizational factors that are believed to explain knowledge-sharing behaviour. A dataset was collected from 203 academic staff members working at a public university in Vietnam. Pearson's correlation and multiple regression analyses were used to analyse the data. The results indicated that two components of the organizational factors, trust and organizational support, were positively and significantly related to knowledge sharing, whereas information technology did not influence knowledge sharing. The findings also show strong, significant positive relationship between extroversion and knowledge-sharing behaviour, whereas, there is a negative relationship between introversion and knowledge-sharing behaviour. The findings also show that perceived reciprocal benefits and reputation enhancement have strong influences on knowledge-sharing behaviour.
Keywords: 650; higher education; knowledge management; knowledge-sharing; knowledge-sharing behaviour; university autonomy